2017
DOI: 10.1007/s11214-017-0439-4
|View full text |Cite
|
Sign up to set email alerts
|

OSIRIS-REx Contamination Control Strategy and Implementation

Abstract: OSIRIS-REx will return pristine samples of carbonaceous asteroid Bennu. This article describes how pristine was defined based on expectations of Bennu and on a realistic understanding of what is achievable with a constrained schedule and budget, and how that definition flowed to requirements and implementation. To return a pristine sample, the OSIRIS- REx spacecraft sampling hardware was maintained at level 100 A/2 and <180 ng/cm2 of amino acids and hydrazine on the sampler head through precision cleaning, con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…The species and the abundance of amino acids on our witness coupons are similar to what was found on those reported by the NASA/JSC OSIRIS-REx team (Dworkin et al 2018;McLain et al, 2015, Contamination Knowledge Report JSC Curation Cabinets, personal communication). The NASA/JSC OSIRIS-REx team investigated the contamination level of cabinet desiccator boxes located in an ISO 7 cleanroom at Johnson Space Center (JSC) that were reserved for the storage of OSIRIS-RExreturned samples.…”
Section: Inter-laboratory Evaluation Of Witness Coupons Between the Nsupporting
confidence: 88%
See 3 more Smart Citations
“…The species and the abundance of amino acids on our witness coupons are similar to what was found on those reported by the NASA/JSC OSIRIS-REx team (Dworkin et al 2018;McLain et al, 2015, Contamination Knowledge Report JSC Curation Cabinets, personal communication). The NASA/JSC OSIRIS-REx team investigated the contamination level of cabinet desiccator boxes located in an ISO 7 cleanroom at Johnson Space Center (JSC) that were reserved for the storage of OSIRIS-RExreturned samples.…”
Section: Inter-laboratory Evaluation Of Witness Coupons Between the Nsupporting
confidence: 88%
“…The difference in the common species of amino acids between the two facilities may be attributed to the origins of the contaminants. Through luminosity analysis, Dworkin et al (2018) found that the total abundance on the NASA/JSC witness plates could not be explained only by the presence of viable cells on the witness plates. Thus, several other organic materials in the cleanroom could also have been the source of the amino acids.…”
Section: Inter-laboratory Evaluation Of Witness Coupons Between the Nmentioning
confidence: 99%
See 2 more Smart Citations
“…OSIRIS‐Rex; Dworkin et al. ). Carbonaceous materials are affected by electron, ion, and synchrotron radiation beams.…”
Section: Discussionmentioning
confidence: 99%